Competition Law and Economic Regulation Addressing Market Power in Southern Africa - Zengeni, Tatenda (Wits University Press, 2017)
Shaping markets through competition and economic regulation is at the heart of addressing the development challenges facing countries in southern Africa. The contributors to 'Competition Law And Economic Regulation: Addressing Market Power In Southern Africa' critically assess the efficacy of the competition and economic regulation frameworks, including the impact of a number of the regional competition authorities in a range of sectors throughout southern Africa. Featuring academics as well as practitioners in the field, the book addresses issues common to southern African countries, where markets are small and concentrated, with particularly high barriers to entry, and where the resources to enforce legislation against anti-competitive conduct are limited. What is needed, the contributors argue, is an understanding of competition and regional integration as part of an inclusive growth agenda for Africa. By examining competition and regulation in a single framework, and viewing this within the southern African experience, this volume adds new perspectives to the global competition literature. It is an essential reference tool and will be of great interest to policymakers and regulators, as well as the rapidly growing ecosystem of legal practitioners and economists engaged in the field.